RESULTS OF BIOCHEMICAL EXAMINATION OF PATIENTS WITH INFLAMMATORY DISEASES OF THE NOSE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Infectious diseases, despite modern treatment and prevention capabilities, remain the main pathology of the population. Today it is believed that from 1 to 5% of all patients with acute respiratory diseases, including influenza, have signs of infectious myocarditis. The true frequency is very difficult to establish, since latent and mild forms, most characteristic of childhood, range from 24 to 33%, are rarely diagnosed and end independently in the absence of any special treatment or transform into a chronic process with nonspecific symptoms.